Effect of high-pressure on protein structure, refolding, and crystallization - Alberto Baldelli; Jiahua Shi; Anika Singh; Yigong Guo; Farahnaz Fathordoobady; Amir Amiri; Anubhav Pratap-Singh (Food Chemistry Advances, 2024)
High-pressure processing (HPP) has been employed in the food and pharmaceutical industries for multiple applications, such as microbial inactivation, shelf life extension, homogenizing/stabilizing emulsions, suspensions, gels, and other colloidal systems, cold extraction of meat in crustaceans, the opening of mollusks, etc. However, high pressure is known to affect the stability and the quality of barosensitive (i.e., sensitivity because of the level of pressure) components of the bioproducts, such as proteins. In general, Le Chatelier's principle dictates the fate of high molecular weight polymeric compounds like proteins under high pressure, suggesting a tendency to degrade into simpler monomers. From a structural analysis point of view, this generally results in increased tendencies for the protein to denature from its native state and possibly affect its ability to renature. Protein crystallization is also affected favorably or unfavorably by pressure, depending on the effect of pressure on nucleation and crystal growth steps for the particular type of protein. Protein refolding is another effect whose kinetics can be optimized by pressure. This work discusses the mechanisms of the impact of pressure on protein structure, crystallization refolding, and unfolding, with examples of the application of these processes in recent literature.